GENDER REPRESENTATION IN THE NATIONAL ASSESSMENTS OF MATHEMATICAL ACHIEVEMENTS - Grigaliūnienė, Monika; Kačinskaitė, Roma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Balanced gender representation allows stereotype threat effect to be avoided so it is important in any type of educational materials, but it is even more so in national assessments as in some cases their outcome determines opportunities for young people. This study is centered on gender representation in the country-wide [Lithuanian] assessments of students' mathematical knowledge and skills, particularly, on the national assessments and exams level. The research data was analyzed using the authors' evaluation matrix. There were seven categories of topics found in contextual problems: free time and socialization, housework, movement, sagacity, shopping, skillfulness and sports. Study shows that some types of assessments represent genders in a more balanced way than others. When compared to other educational or entertainment sources of written information, national assessments of mathematical achievements seems to represent gender in a more balanced way.